2005
DOI: 10.1136/jnnp.2004.055160
|View full text |Cite
|
Sign up to set email alerts
|

Recanalisation of middle cerebral artery occlusion after intra-arterial thrombolysis: different recanalisation grading systems and clinical functional outcome

Abstract: Background: Different grading systems of arterial recanalisation have never been compared in large series of stroke patients treated with intra-arterial thrombolysis (IAT). Methods: Clinical and angiographic findings and outcome were analysed in 147 patients with M1 or M2 segment occlusion of the middle cerebral artery treated with IAT. Associations of the thrombolysis in myocardial infarction (TIMI) grading system and the Mori grading system with clinical outcome were compared. Results: The median NIHSS score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 16 publications
1
33
1
Order By: Relevance
“…There are several schema available for classifying angiographic results, including the Mori scale, 5 TIMI, the arterial occlusive lesion score from IMS, and the original TICI and the modified TICI, with 2a and 2b defined separately. The relationship between these schema and outcomes, including comparison of TIMI and Mori schemes and comparison of outcomes based on TIMI, has also been done, 13 with both of those series suggesting a benefit to partial reperfusion. However, the definition of partial reperfusion is key, with TIMI 2 (encompassing both 2a and 2b) considered partial reperfusion in both of those series.…”
Section: Discussionmentioning
confidence: 99%
“…There are several schema available for classifying angiographic results, including the Mori scale, 5 TIMI, the arterial occlusive lesion score from IMS, and the original TICI and the modified TICI, with 2a and 2b defined separately. The relationship between these schema and outcomes, including comparison of TIMI and Mori schemes and comparison of outcomes based on TIMI, has also been done, 13 with both of those series suggesting a benefit to partial reperfusion. However, the definition of partial reperfusion is key, with TIMI 2 (encompassing both 2a and 2b) considered partial reperfusion in both of those series.…”
Section: Discussionmentioning
confidence: 99%
“…13 Patients with no reperfusion were classified as Mori 0, patients between 0% and 50% reperfusion were classified as Mori 1, patients between 50% and 100% reperfusion were classified as Mori 2, and patients with 100% reperfusion were classified as Mori 3.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent evaluation of the Mori grading system demonstrated association with clinical outcome and suggested that the expanded distinction of reperfusion categories may improve outcome prediction. 14 …”
mentioning
confidence: 99%
“…13 Some applications of the TIMI scale that have been associated with clinical functional outcomes have been demonstrated in studies of intra-arterial thrombolysis for AIS. 13,14 The variability in the operating manual/grading definition of the TIMI scoring system is the main disadvantage of its use across clinical trials; however, its biggest advantage is its simplicity and familiarity to many stroke neurologists and neurointerventionalists.…”
mentioning
confidence: 99%